The Theory of Graphs and Its Applications - Burger, E.; Berge, Claude; Doig, A. (Econometrica, 1965)
This book on the theory of graphs provides the reader with a mathematical tool which can be used in the behavioral sciences, in the theory of information, cybernetics, games, transport networks, as well as in set theory and matrix theory.